Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/01.mcp.0000239551.47702.f4
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in ankylosing spondylitis

Abstract: The clinical significance of the high-resolution computed tomography abnormalities remains to be determined. Most of the published studies are cross-sectional, and are limited by lack of control subjects matched for age, gender and tobacco use. Studies to correlate high-resolution computed tomography changes with bronchoalveolar lavage and lung biopsies as well as prospective studies on long-term evolution of these findings including those patients receiving anti-tumor necrosis factor-alpha agents are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
1
31
0
4
Order By: Relevance
“…Finally, Sampaio-Barros et al [34] showed HRCT abnormalities in 40% of 52 patients, presenting non-specific parenchymal opacities (19%) as the most common type of involvement. In summary, HRCT changes were found to be prevalent in AS even in patients with early disease, and in those with normal chest radiographs and without respiratory symptoms [35,36]. In the present study, we detected HRCT abnormalities in 70% of 20 male AS patients without respiratory symptoms.…”
Section: Discussionmentioning
confidence: 39%
“…Finally, Sampaio-Barros et al [34] showed HRCT abnormalities in 40% of 52 patients, presenting non-specific parenchymal opacities (19%) as the most common type of involvement. In summary, HRCT changes were found to be prevalent in AS even in patients with early disease, and in those with normal chest radiographs and without respiratory symptoms [35,36]. In the present study, we detected HRCT abnormalities in 70% of 20 male AS patients without respiratory symptoms.…”
Section: Discussionmentioning
confidence: 39%
“…In this context, reduction maneuvers have the potential to cause injury to the diseased and weakened aorta. 17,29 Pulmonary function can also be impaired due to pulmonary fibrosis, interstitial lung disease, pleural thickening, and chronic pleural effusions, 33 many of which are clinically silent until late in the disease process or until events such as SCI. Decreased aerobic capacity and poor pulmonary function 13 are common in the patient with AS and appear to be directly related to deconditioning.…”
Section: Special Considerations In Thementioning
confidence: 99%
“…Zamanla tutulumun sakroiliyak eklemlerden servikal bölgeye doğru ilerlemesiyle postür öne fleksiyon yönünde bozulmakta, hastanın hareketleri günlük yaşam aktivitelerini etkileyecek ölçüde kısıtlan-maktadır (2). Hastalığın seyrinde göz tutulumu, renal, kardiyovasküler ve pulmoner tutulumla nadiren nörolo-jik komplikasyonlar görülebilmektedir (3). AS'li hastalarda kostovertebral eklemlerin füzyonu sonucu kostaların normal hareketinin bozulması nedeniyle göğüs duvarı ekspansiyonu önemli ölçüde kısıtlanmaktadır.…”
Section: Introductionunclassified
“…1984 Modifiye New York Kriterlerine göre dördüncü interkostal aralıktan ölçülen göğüs ekspansiyonunun normalden daha az olması, AS için tanı kriterleri arasında yer almaktadır (1). AS'li hastalarda genellikle restriktif solunumsal bozukluklar tanımlanmakta ve solunumsal anomalilerden daha çok göğüs duvarı mobilitesinin azalması sorumlu tutulmaktadır (3). Genel olarak ağrı, eklem hareket kısıtlılıkları ve pulmoner sistemin etkilenimi sonucu gelişen dispne hissi hastaların günlük yaşam aktivitelerini gerçekleştirmede güçlük ve yaşam kalitelerinde azaltma yaratmaktadır (4).…”
Section: Introductionunclassified